Improvement of Real-Time Hybrid Simulation Using Parallel Finite-Element Program. Issue 10 (2nd October 2020) - Lu, Li-Qiao; Wang, Jin-Ting; Zhu, Fei
ABSTRACT: This paper proposes a novel framework to efficiently calculate a large-scale finite element (FE) numerical substructure in real-time hybrid simulation (RTHS). It is composed of a non-real-time Windows computer and a real-time Target Computer. The Windows computer is used to solve the FE numerical substructure by parallel computing in soft real-time, while the real-time Target Computer generates displacement signals for the controller in real time. Based on the proposed framework, a RTHS with numerical substructure simulated in Windows environment is developed. It is demonstrated that the computational efficiency of the RTHS could be greatly improved by parallel programming.